Economic growth and development lessons from the experience of Cyprus : a small island economy - Matsis, Symeon (World Bank WashingtonUS, 1999)
Attempts to identify the major factors, which explain the successful economic and social development of Cyprus, to be used to draw conclusions which could be of help to other small economies in their quest for economic growth and development.